Underweight among Children under TwoYears in Indonesia - Zahrotu Romadhon; Hario Megatsari; AgungDwi Laksono; Mursyidul Ibad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Underweight, have an impact on low cognitive, productivity, and intellectual abilities in children. Thisstudy aimed to analyze ecologically the factors related to underweight among children under two years inIndonesia.The study conducted using secondary data from the Indonesia Ministry of Health official report.Apart from the prevalence of underweight in children under two years, four other variables analyzed asindependent variables were the percentage of population passing Junior High School, poor population,exclusive breastfeeding, and prevalence of low birth weight.Data were analyzed using cross-tabulation.The results showed there was no relationship between the prevalence of underweight in children under twoyears with the percentage of population passing Junior High School and the percentage of poor population.Meanwhile, there is a positive relationship between the prevalence of low birth weight with the prevalenceof underweight in children under two years. The higher the prevalence of low birth weight, the higher theprevalence of underweight in children under two years. Moreover, the study found the higher the percentageof exclusive breastfeeding, the lower the prevalence of underweight in children under two years in a region.The study concluded that ecologically two variables have an ecological relationship with the prevalence ofunderweight in children under two years, namely the prevalence of low birth weight and the percentage ofexclusive breastfeeding.